On stability in the maximum norm of difference scheme for nonlinear parabolic equation with nonlocal condition - Sapagovas, Mifodijus; Novickij, Jurij (Nonlinear Analysis: Modelling and Control, 2023)
We construct and analyze the backward Euler method for one nonlinear one-dimensional parabolic equation with nonlocal boundary condition. The main objective of this article is to investigate the stability and convergence of the difference scheme in the maximum norm. For this purpose, we use the M-matrices theory. We describe some new approach for the estimation of the error of solution and construct the majorant for it. Some conclusions and discussion of our approach are presented.
Keywords: parabolic equation; nonlocal boundary conditions; M-matrices; stability analysis